2011
DOI: 10.1118/1.3612200
|View full text |Cite
|
Sign up to set email alerts
|

SU‐E‐T‐249: Evaluation of the Surface Rendering Patient Localization System for Proton Therapy Facility

Abstract: Purpose: Proton therapy carries a number of dosimetric and radiobiological advantages for cancer patients and calls for rigorous quality assurance of patient registration. This work is a report of evaluation and use of surface rendering patient positioning system (AlignRTTM) in proton facility. Method and Materials: The AlignRT three‐camera system was installed in a specific non‐symmetric geometry, specific to the proton gantry room. Series of phantom shifts/rotations were done to assess the system performance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Gantry motion or imaging equipment in the proton vault may block the view of the SGRT camera positions, causing suboptimal operation of the SGRT system. One proton center had to relocate the SGRT cameras to a nonsymmetric arrangement, 10 whereas another group reported that the camera placement was dictated by the design of the proton vault. 11 The Maastro Clinic proton therapy center (Maastricht, the Netherlands) had to install a nonstandard SGRT camera system because the image isocenter was located away from the treatment isocenter for CBCT imaging.…”
Section: Introductionmentioning
confidence: 99%
“…Gantry motion or imaging equipment in the proton vault may block the view of the SGRT camera positions, causing suboptimal operation of the SGRT system. One proton center had to relocate the SGRT cameras to a nonsymmetric arrangement, 10 whereas another group reported that the camera placement was dictated by the design of the proton vault. 11 The Maastro Clinic proton therapy center (Maastricht, the Netherlands) had to install a nonstandard SGRT camera system because the image isocenter was located away from the treatment isocenter for CBCT imaging.…”
Section: Introductionmentioning
confidence: 99%